A Contrastive Study of Boosters in a Corpus of Academic Spoken English - Wazni, Ali khudhair Abd Oun; Mansouri, Sara; Sattar Boroujeni, Sousan (BELT - Brazilian English Language Teaching Journal, 2023)
The present study intended to investigate the use of boosters in the Michigan Corpus of Academic Spoken English (MICASE). It examined whether native and non-native speakers of English differed from each other in boosters’ use based on Hyland (2005) across academic divisions, levels of interactivity, genders, and academic roles in academic spoken English. The results of the UNIANOVA inferential test revealed that not only did native speakers of English utilize boosters more frequently than non-native ones across the four variables, but they also employed boosters in a way that was specific to academic divisions, levels of interactivity, genders, and academic roles. Besides the influence of culture and proficiency on boosters’ use, this corpus analysis study found that native English speakers put their statements under focus so that they sound convincing to the audience in soft sciences more than the hard ones. It also indicated native speakers’ greater attempt to convince their audience of the truth in their propositions, show new pieces of information as true, and back their own manipulative or persuasive purposes in highly interactive speeches more than the other levels of interactivity. Furthermore, it was shown that female native speakers exceeded to express opinions, state a suggestion with confidence in their knowledge of the topic, and minimize the possibility of accepting other options in academic spoken English of the MICASE. Ultimately, it illustrated that native academic speakers of English of faculty role rated higher to strengthen their existence, position, argument, claims, and commitment to their speech.